1993
DOI: 10.1002/pd.1970130713
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of gastrointestinal obstruction: A correlation between prenatal ultrasonic findings and postnatal operative findings

Abstract: The impact of prenatal sonographic diagnosis of oesophageal and gastrointestinal obstructions has been analysed over a 10-year period. Three groups of patients were evaluated. The first group consisted of 46 newborns with abnormal prenatal sonograms, 41 of which were confirmed to have intestinal obstruction postnatally. The second group consisted of 17 neonates with normal prenatal sonograms who had intestinal obstruction postnatally. The third group included 56 newborns who did not undergo a prenatal sonogram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…In two other studies, in cases diagnosed prenatally the ages of the newborns at postnatal confirmation of diagnosis and at surgery were significantly younger, resulting in fewer metabolic complications 10 and a significantly earlier start of intestinal feeding 11 . However, there have been other studies in which no difference in overall outcome was demonstrated, and this was mainly attributed to the high incidence of associated major anomalies 4,12 . In these and in other studies 13 -15 , the outcome for fetuses and infants with or without associated anomalies was not assessed separately.…”
Section: Introductionmentioning
confidence: 94%
“…In two other studies, in cases diagnosed prenatally the ages of the newborns at postnatal confirmation of diagnosis and at surgery were significantly younger, resulting in fewer metabolic complications 10 and a significantly earlier start of intestinal feeding 11 . However, there have been other studies in which no difference in overall outcome was demonstrated, and this was mainly attributed to the high incidence of associated major anomalies 4,12 . In these and in other studies 13 -15 , the outcome for fetuses and infants with or without associated anomalies was not assessed separately.…”
Section: Introductionmentioning
confidence: 94%
“…In two other studies, in cases diagnosed prenatally the ages of the newborns at postnatal confirmation of diagnosis and at surgery were significantly younger, resulting in fewer metabolic complications10 and a significantly earlier start of intestinal feeding11. However, there have been other studies in which no difference in overall outcome was demonstrated, and this was mainly attributed to the high incidence of associated major anomalies4, 12. In these and in other studies13–15, the outcome for fetuses and infants with or without associated anomalies was not assessed separately.…”
Section: Introductionmentioning
confidence: 99%
“…The prenatal sonographic diagnosis of lower intestinal obstruction has been established (Dell'Agnola et al, 1993;Hertzberg, 1994). However, most cases were diagnosed in the second half of pregnancy, mainly in the third trimester.…”
Section: Introductionmentioning
confidence: 99%